Chemoselective one‐pot synthesis of terphenyl derivatives by sequential directed C―H functionalization–Suzuki coupling. (2nd July 2014) - Ren, Limin; Chu, Wenyi; Guan, Dinghui; Hou, Yanjun; Wang, Man; Yuan, Xiaobin; Sun, Zhizhong
<x xml:space="preserve">Abstract</x> A simple and efficient route for the preparation of terphenyl derivatives via palladium‐catalyzed sequential directed C―H arylation/Suzuki–Miyaura cross‐coupling in 'one‐pot' has been developed. 4, 4′‐(Cyclohexane‐1, 1‐diyl)diphenol is an essential ligand. This reaction can tolerate a series of functional groups and provides the terphenyl derivatives in moderate to good yield. Copyright © 2014 John Wiley & Sons, Ltd.